Effect of graphene infusion on morphology and performance of natural rubber latex/graphene composites - Rahman, Marlinda Ab; Goh, Boon Tong; Kamaruddin, Nurul Hazierah; Wahab, Fadilah Abd; Hamizi, Nor Aliya; Chowdhury, Zaira Zaman; Sagadevan, Suresh; Chanlek, Narong; Johan, Mohd Rafie (Springer, 2019)
Nowadays developments of most flexible electronic devices have significantly increased due to high demand on healthcare applications of daily life activities. Given these development factors, the production of nanoparticles-polymer composite improves the functionality of stretchable or improves interfacial adherence between the matrix and nanoparticles. In this research work, graphene used as functional filler materials into the polymer (natural rubber latex) matrices is presented. The surface morphology of pure natural rubber latex (NRL) and natural rubber latex/graphene (NRL/G) composite were observed by using Scanning electron microscopy (SEM). The X-ray photoelectron spectroscopy (XPS) was recorded to investigate the elements and functional groups present in the graphene and NRL and in the NRL/G composite. Furthermore, the mechanical and conductivity properties of the pure NRL and NRL/G composite are studied. The mechanical property and conductivity test were performed by a universal testing machine and two-point probes measurement respectively. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.